2020
DOI: 10.1016/j.joms.2020.07.012
|View full text |Cite
|
Sign up to set email alerts
|

The Early Effects of Coronavirus Disease-2019 on Head and Neck Oncology and Microvascular Reconstruction Practice: A National Survey of Oral and Maxillofacial Surgeons Enrolled in the Head and Neck Special Interest Group

Abstract: Purpose The coronavirus disease-2019 (COVID-19) pandemic has affected healthcare systems across the nation. The purpose of this study is to gauge the early effects of the COVID-19 pandemic on head and neck oncology and reconstructive surgery (HNORS) practice and evaluate their practice patterns especially ones that might be impacted by COVID-19 and compare them to the current literature. Methods This study is a cross-sectional study that surveyed fellowship-trained oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…Microvascular reconstruction continues to be the standard of care at a few centres with adequate resources. However, pedicled flaps being the work-horse can be considered in present circumstances where patients may be managed outside an intensive or high dependency unit with rapid turnover [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microvascular reconstruction continues to be the standard of care at a few centres with adequate resources. However, pedicled flaps being the work-horse can be considered in present circumstances where patients may be managed outside an intensive or high dependency unit with rapid turnover [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…El número de procedimientos quirúrgicos también sufrió una caída, aunque la variación dependió del país, el tipo de práctica y el momento de la pandemia 17,18 . La estrategia desarrollada permitió que esta diminución no fuera tan dramática, lo que contrasta con reportes de supresión de casi el 100 % de la practica quirúrgica en hasta el 17 % de los servicios 18 .…”
Section: Discussionunclassified
“…[1] A national survey of Oral and Maxillofacial surgeons on early effects of the pandemic on head and neck oncology and microvascular reconstruction practice reported that 8% were requested to pause head and neck cancer (HNC) surgery, 24% to pause free flap surgery, while 55% agreed that head and neck and reconstructive surgery should continue. [2] Jeannon reported their units continued provision of complex HNC surgery during the pandemic, focused on a two-month period and comprising only 13 patients with microvascular free tissue transfer who were highly selected as low-risk candidates. [3] In our Unit, the pandemic caused difficulties accessing theatres but contingencies allowed for cancer ablative surgery and free flap reconstruction to continue.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly Zaid reported that most surgeons (92%) kept their patients in an intensive care unit (ICU) environment, whereas only 8% transferred them to a specialized step-down unit. [2] …”
Section: Introductionmentioning
confidence: 99%